(untitled) (Psychology Travelogs, 2023)
The article highlights the pressing issue of restoring and preserving mental health in Ukraine, emphasizing the need for effective strategies across various professional fields. It underscores the importance of identifying personal resources for self-preservation, fostering the ability to overcome environmental challenges, crises, and extreme situations while maintaining emotional balance. Research indicates that anxiety, rooted in negative social environments during early life, can persist throughout one’s lifespan, negatively impacting mental health. The study explores the interconnection between anxiety and mental health, particularly in adolescents and high school students. While existing literature often views anxiety as a genetically, ontogenetically, or situationally determined mental property, this study focuses on the relationship between anxiety and mental health as an independent research area. The COVID-19 pandemic and war have intensified researchers’ interest in this issue, particularly concerning adolescents and high school students, who may experience various psychological difficulties, conflicts, and disruptions in psychological defense mechanisms. The concept of anxiety is defined as a complex process involving cognitive, affective, and conative reactions in situations perceived as potentially dangerous by the individual. High levels of personal anxiety manifest as a tendency to perceive the environment as threatening and a strong desire to ensure personal safety, often leading to self-imposed restrictions. The article suggests that family members play a crucial role in the restoration and preservation of their children’s mental health, necessitating the preparation of parents for effective psychotherapeutic functions - a prospect for future research.